Left atrial performance during exercise in endurance athletes: the impact of gender. (25th November 2020) - Simard, F; Sanz-De La Garza, M; Vaquer-Segui, A; Blanco, I; Prat-Gonzalez, S; Bijnens, B; Sitges, M
Abstract: Background: High-intensity endurance training is associated with an increased risk of atrial fibrillation (AF) in male athletes while it seems to have a protective effect for the development of atrial arrhythmias in female athletes. Mechanisms underlying this fact are unknown but a differential atrial adaptation to exercise may be involved. Aim: To evaluate left atrial (LA) performance during exercise in endurance athletes (EAs) of both sexes. Methods: Highly-trained (>10 hours training/week) EAs performed a maximal cardiopulmonary exercise test. LA evaluation was performed at rest and immediately after exercise. LA analysis consisted of standard and speckle-tracking assessment: atrial contractile, reservoir and conduction strain. Results: 80 EAs (55% women, 34.8±5.8 years) were enrolled. Baseline LA size and functional parameters were similar in both sexes (Table 1). Compared to men, women achieved a higher predicted VO2max (Δchange+11.9%, p<0.01) but a similar increase of systolic blood pressure (Δ+63 vs +66%, p=0.58). Exercise induced a mild decrease in LA size but of similar amplitude for both sexes. LA strain parameters of EAs improved with exercise, but a significantly greater improvement in LA reservoir and conduit function was noted in women compared to men. In EAs with marked atrial remodelling (LA ≥35ml/m 2 ), the same trend of greater improvement of LA reservoir and conduit function in women persisted. Conclusion: In highly-trained EAs, premenopausal women have better LA function profile during exercise compared to men, even when the LA is significantly dilated. This discriminatory LA adaptation in female EAs could at least partly explain the dichotomous relationship between AF and exercise regarding sexes and warrants further studies to clarify the underlying mechanism. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Government of Spain - Plan Nacional I+D, Ministerio de Economia y Competitividad